2021
DOI: 10.1192/bjo.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Victimisation of individuals with serious mental illness living in sheltered housing: differential impact of risk factors related to clinical and demographic characteristics

Abstract: Background Sheltered housing is associated with quality-of-life improvements for individuals with serious mental illness (SMI). However, there are equivocal findings around safety outcomes related to this type of living condition. Aims We aimed to investigate raw differences in prevalence and incidence of crime victimisation in sheltered housing compared with living alone or with family; and to identify groups at high risk for victimisation, using demographic and clinical factors. We do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The elevated risk of shared sheltered housing, in contrast to single housing, remained significant after adjusting for sociodemographic and a variety of clinical characteristics, suggesting that mechanisms unique to those housing arrangements pose an independent risk for its inhabitants. The downsides of sheltered housing have been described before, however often in the context of qualitative studies (71)(72)(73)(74). We suggest the staff of sheltered housing to remain alert for crime incidents, monitoring both co-habitants as well as contact from the wider community.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The elevated risk of shared sheltered housing, in contrast to single housing, remained significant after adjusting for sociodemographic and a variety of clinical characteristics, suggesting that mechanisms unique to those housing arrangements pose an independent risk for its inhabitants. The downsides of sheltered housing have been described before, however often in the context of qualitative studies (71)(72)(73)(74). We suggest the staff of sheltered housing to remain alert for crime incidents, monitoring both co-habitants as well as contact from the wider community.…”
Section: Discussionmentioning
confidence: 75%
“…Living in sheltered housing was found to be a potential risk factor especially for property crime victimization, impacting both prevalence and frequency rates. This is particularly poignant since sheltered living is supposed to protect and facilitate recovery of vulnerable patients (71). The elevated risk of shared sheltered housing, in contrast to single housing, remained significant after adjusting for sociodemographic and a variety of clinical characteristics, suggesting that mechanisms unique to those housing arrangements pose an independent risk for its inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…Research employing longitudinal and cross-sectional designs has reported associations between early life trauma, chronic health problems, and mental health disorders (15)(16)(17)(18)(19)(20)(21). Exposure to four different types of adverse childhood events (ACE) is strongly associated with problematic poor mental health, drug use, and self-directed violence (22).…”
Section: Introductionmentioning
confidence: 99%